2005
DOI: 10.1155/2005/318294
|View full text |Cite
|
Sign up to set email alerts
|

The Laboratory Diagnosis of Herpes Simplex Virus Infections

Abstract: Herpes simplex virus (HSV) types 1 and 2 cause genital herpes infections and are the most common cause of genital ulcer disease in industrialized nations. Although these infections are very common, the majority of them remain underdiagnosed because they are asymptomatic or unrecognized. A clinical diagnosis of genital herpes should always be confirmed by laboratory testing; this can be accomplished through the use of direct tests for viral isolation, the detection of antigen or, more recently, the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 43 publications
0
52
0
3
Order By: Relevance
“…Existen otros métodos diagnósticos directos, entre los que se encuentran el aislamiento viral mediante cultivo (método de elección para distinguir entre herpes virus tipo 1 o 2), la detección del antígeno viral mediante inmunofluorescencia directa, la microscopía electrónica (no distingue el tipo de herpes) y la detección del ADN viral mediante técnicas de hibridación [5,9].…”
Section: Discussionunclassified
“…Existen otros métodos diagnósticos directos, entre los que se encuentran el aislamiento viral mediante cultivo (método de elección para distinguir entre herpes virus tipo 1 o 2), la detección del antígeno viral mediante inmunofluorescencia directa, la microscopía electrónica (no distingue el tipo de herpes) y la detección del ADN viral mediante técnicas de hibridación [5,9].…”
Section: Discussionunclassified
“…Clear differences were noted in hepatitis C risk behaviors. Men had higher rates of lifetime drug-related risk behaviors: due to needle use needle sharing and crack cocaine use [20]. Recently, HCV prevalence studies have been reported from Pakistan and Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, laboratory testing methods are routinely used to support the diagnosis. Viral culture was once the gold standard for HSV diagnosis, but as a result of the long turnaround time and reduced sensitivity of the method compared with molecular testing, viral culture for HSV has largely fallen out of favor (39 ). Nucleic acid testing by PCR assay of a swab of a lesion is highly sensitive in an individual presenting with active lesions (40,41 ).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Of those subtypes, Ͼ40 can infect the genital tract. Subtypes 6 and 11 are most often associated with genital warts, whereas infection with high-risk subtypes including 16,18,31,33,35,39,45,51,52,56,58,59,66, and 68 are linked to cervical and rectal neoplasia (81 ).…”
Section: Human Papilloma Virusmentioning
confidence: 99%